Metode Pemulusan Eksponensial Tripel Tipe Brown pada Peramalan Pajak Restoran dan Hotel Kota Padang - Bonita Nurul Afifah; Helma Helma; Dony Permana (Journal of Mathematics UNP, 2018)
Abstract – This research discuss about forecasting of the total restaurant and hotels tax at Padang City use a method of exponential smoothing triple tipe Brown. The fact is the number of visitors hotel and restaurants comes not constant or not sure yet on each year. Therefore the method forecasting can be a right solution is estimate that the number of the tax restaurant and hotel in future time. The purpose on this research is to estimate receipt of the number of the tax hotel and restaurants at Padang City on the next five years. The method used to forecast the number of the tax restaurant and hotel at Pada City of the is the method of exponential smoothing triple tipe Brown. Based on the research results obtained by the model exponential smoothing triple tipe Brown the right to use in forecasting revenue amount restsurant and hotels tax at Padang City is F_(10+m)=51.688.474.068+7.812.509.304m+349.042.638,65m^2, with the number of periods (m) is one until five.